Periodismo y Ciudadanía Plural: problemas, rutinas y retos - Moreno Sardà, Amparo; Simelio Solà, Nuria; Rovetto Gonem, Florencia; Buitrago Londoño, Alfonso (Estudios sobre el Mensaje Periodístico, 2007)
Several researches bring about by the group Women and Mass Culture Feminary, from the Department of Journalism and Communication Sciences at University of Barcelona (UAB), have driven attention to the fact that at the Spanish press, since the transition to democracy after several decades of dictatorship, some routines of the news making process persist and avoid newspapers to properly inform about important social transformations occurred since the begging of the democratic process in Spain. It is argued that the press is stuck in an androcentric point of view or way of scoping reality, restrictive to adult men related to power centres of politics, economics and cultural life. In addition, it is also argued that this preferred attention to power centres has become more abstract; more dehumanized moving far away from regular people.